Most Subversive Suffering: Pain and the Reversal of Roles in Graeco-Roman Antiquity - Laes, Christian (Hyperboreus, 2022)
This paper asks whether Graeco-Roman culture bears any traces of voluntary indulging in pain and punishment as a form of sexual game. In order to answer such a question, the context of slavery and the use of violence in education needs to be acknowledged first. After this, I look for traces in ceremonies, iconography, love poetry, and role playing by children. More than a century ago, scholars had already tried to identify sado-masochism in Antiquity. Though such is surely an anachronistic approach, a careful inquiry of pain and reversal of roles reveals vital features of ancient society.